Triiodothyronine Potentiates BMP9-Induced Osteogenesis in Mesenchymal Stem Cells Through the Activation of AMPK/p38 Signaling - Chen, Xiaoting; Hu, Yan; Jiang, Tianyuan; Xia, Chao; Wang, Yan; Gao, Yanhong (Frontiers in Cell and Developmental Biology, 2020)
Thyroid hormone (TH), triiodothyronine (T3) and thyroxine (T4), which are released from the thyroid, control many cellular processes in various cell types. It is worth noting that TH plays a complex role in skeletal metabolic balance, and few studies have investigated whether TH exerts any effects on osteogenesis in bone mesenchymal stem cells (MSCs). We explored the effects of T3 on bone morphogenetic protein 9 (BMP9)-induced osteogenesis, which process is considered the most important in the osteogenic differentiation of C3H10T1/2 cells. In vitro osteogenesis was analysed by alkaline phosphatase (ALP) activity and staining, bone mineralisation and osteocalcin and osteopontin expression. Foetal limb explant cultures and ectopic MSC implantation further confirmed the role of T3. Finally, we examined the effect of AMPK/p38 signalling on the osteoblastic differentiation. T3 synergizes with BMP9 to enhance osteogenic marker expression induced by BMP9. Furthermore, T3 promotes BMP9-induced bone formation by foetal limb explant cultures and ectopic MSC implantation. Co-treatment with BMP9 and T3 can promote AMPK and p38 phosphorylation, and pretreatment with the AMPK inhibitor compound C and siRNA can abolish phosphorylation of p38 and BMP9+T3-induced ALP activity. Our results suggest that BMP9 and T3 promote osteogenic differentiation at least partially via the activation of the AMPK/p38 signalling pathway.